Impact of land use change and rapid urbanization on urban heat island in Kolkata city: A remote sensing based perspective - Chatterjee, Uday; Majumdar, Sushobhan (Journal of urban management, 2022)
Kolkata is one of the cities located in the eastern parts of India and experiences rapid urban growth. Because of the rapid urbanization, land use and land cover are changing very rapidly in which impacts on the local land resources and the surface temperature of Kolkata are much higher than its surroundings. In this study, an effort has been done to find out how the vegetation cover is affected by urban growth and how the built up area grew over time. Except this, the attempt has also been made to scrutinize the trends of surface temperature in Kolkata city. This study was done between 2005 and 2019. To find out the vegetation cover and built up area of Kolkata city, Normalized Difference Vegetation Index and Normalized Difference Built up Area Index and Landsat satellite images between the year 2005 and 2019 have been used. This study reveals that vegetation area is declining towards the city core areas and percentages of built up areas are increased towards the urban area. Surface temperature is high in the city core areas which records 41 ​êC temperature in 2019. This study will throw new light in case of urban heat island studies.